Facilitating Torrance Tests of Creative Thinking Use in Malaysian TVET Research: The Initial Step Of Inter-Rater Reliability Determination - Madar, Ahmad Rizal; E.S, Chew; Hamid, & Hashima (Journal of Technical Education and Training, 2019)
Creativity is a valuable 21st century attribute vital  to innovation, and is  considered as an important aspect in technical and vocational education and training (TVET). This study is prompted by the lack of international test use in Malaysian TVET creativity -related research and the Torrance Tests of Creative Thinking (TTCT), translated into Malay Language (ML) could fill in this gap. The determination of  inter-rater reliability coefficients  cover 5 norm-referenced dimensions or measures of figural creativity, viz. fluency, originality, elaboration, resistance to premature closure,  abstractness of titles, and the overall average score  for the TTCT (Form A).  This study involves correlation research where subjective answers to TTCT (ML) by 35 prospective teachers from Teacher Education Institute - Temenggong Ibrahim Campus, Johor Bahru   were marked by 3 independent inter-ratters, and analysed for correlation.  Data analyses of IRC were carried out using interclass correlation analysis found in the Statistical Package for Social Science (SPSS) software. IRC values were obtained as follows:  fluency (0.99), originality (0.99), elaboration (0.90), resistance to premature closure (0.93), abstractness of titles (0.98), and  overall average score (0.99), with râ‰¥0.9, as at an excellent level. In comparison, these IRC values  for TTCT (ML) version are consistent with values for the English (international) TTCT version, viz. r, from 0.78 to 0.99. In conclusion, with the determination of IRC values for the TTCT (ML) version, Malaysian researchers will have the choice and facilitation to use this set of test instruments to investigate creative, innovative or higher-order thinking skills of their TVET respondents.